2015
DOI: 10.1186/s12864-015-2139-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of the uterine immune response to bacteria during the equine oestrous cycle

Abstract: BackgroundThe steroid hormone environment in healthy horses seems to have a significant impact on the efficiency of their uterine immune response. The objective of this study was to characterize the changes in gene expression in the equine endometrium in response to the introduction of bacterial pathogens and the influence of steroid hormone concentrations on this expression.MethodsEndometrial biopsies were collected from five horses before and 3 h after the inoculation of Escherichia coli once in oestrus (fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 92 publications
2
38
0
Order By: Relevance
“…Our previous next-generation sequencing analysis revealed that a large number of immune response genes were up-regulated within the first 3 h after the introduction of E. coli into the uterus [18]. To investigate the progression of the inflammatory response after this time point, expression of a panel of genes was followed by qPCR until 72 h after inoculation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous next-generation sequencing analysis revealed that a large number of immune response genes were up-regulated within the first 3 h after the introduction of E. coli into the uterus [18]. To investigate the progression of the inflammatory response after this time point, expression of a panel of genes was followed by qPCR until 72 h after inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Genes were chosen for further analysis by PCR based on the analysis of next-generation sequencing data published previously [18]. These included the genes for the Toll-like receptors TLR2 and 4, the NOD-like receptor NLRC5, the chemokines CCL2, CXCL9, CXCL10 and CXCL11, as well as the antimicrobial peptides equine β-defensin 1 (EBD 1), lysozyme, secretory leukoprotease inhibitor (SLPI), secreted phospholipase A 2 (sPLA 2 ), lipocalin 2 (LCN 2), lactoferrin, uteroferrin and the uterocalin precursor (P19).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations